Remission for the corruptor (Between the human right and the spririt for eradication corruption) - HENNY DAMARYANTI; HENDRIK; ANNURDI (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This paper examines the government’s policy of pardoning corrupt officials so that human rights can be upheld and corruption can be eradicated in Indonesia.Methodology: This study is of the normative juridical variety, and its sources are various statutes, documents, and books dealing with the topics of corruption and remission.Findings: This study’s findings indicate that a pardon for a convicted briber is not a free pass for the briber but rather is granted on the condition that the briber agrees to comply with certain rules (such as government legislation and policies) in exchange for his or her release from prison.Novelty/Implications: As a result of corruption’s negative effects on state finances and the general public’s well-being, as well as the widespread corruption directed at those who engage in corrupt behavior, the topic of corruption in Indonesia has recently become a hot topic of discussion. The authors of this paper have tackled a pressing issue and provided policymakers with valuable new information.